Pengaruh Peer Pressure terhadap Academic Stress dengan Self-Control sebagai Moderator - Dhiya' Farkhalina Mayasari; Tri Na'imah; Nur'aeni .; Fatin Rohmah Nur Wahidah (Jurnal Pendidikan Sosial Dan Konseling, 2026)
Academic stress is a common issue faced by students due to the high academic demands. This study aimed to examine the effect of peer pressure on academic stress, with self-control as a moderating variable, among eleventh-grade students. An correlational quantitative approach was employed. The study population comprised 571 students, from whom a sample of 226 eleventh-grade students of Madrasah “X” was selected using simple random sampling. Data were collected using the Student Life Stress Inventory (SLSI), Peer Pressure Inventory (PPI), and Brief Self-Control Scale (BSCS). Data analysis was conducted using Structural Equation Modelling Partial Least Squares (SEM-PLS) with SmartPLS version 4, which involved evaluating both the outer and inner models. The results showed that peer pressure had a significant effect on academic stress. Self-control also had a significant effect on academic stress. However, self-control did not significantly moderate the relationship between peer pressure and academic stress , among eleventh-grade students of Madrasah “X”. Based on these findings, schools are recommended to develop self-management skills programs to help students cope with academic stress.